'Busyness' and the preclusion of quality palliative district nursing care. (December 2013) - Nagington, Maurice; Luker, Karen; Walshe, Catherine
Ethical care is beginning to be recognised as care that accounts for the views of those at the receiving end of care. However, in the context of palliative and supportive district nursing care, the patients' and their carers' views are seldom heard. This qualitative research study explores these views. Data were collected through semi-structured interviews with 26 patients with palliative and supportive care needs receiving district nursing care, and 13 of their carers. Participants were recruited via community nurses and hospices between September 2010 and October 2011. Post-structural discourse analysis is used to examine how discourses operate on a moral level. One discourse, 'busyness', is argued to preclude a moral form of nursing care. The discourse of friendship is presented to contrast this. Discussion explores Gallagher's 'slow ethics' and challenges the currently accepted ways of measuring to improve quality of care concluding that quality cannot be measured.